(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
Tizanidine hydrochloride is a centrally acting skeletal muscle relaxant, used in the management of spasticity. This drug is commercially available only as tablets, which highlights the need to develop oral liquid formulations. In the hospital environment, this aspect is circumvented by the preparation of suspensions, to allow administration to children and adults with impaired swallowing, but there are no data regarding their stability. The purpose of this study was to evaluate the physicochemical andmicrobiological stability of liquid dosage forms prepared in the hospital environment from tizanidine hydrochloride tablets, applying high performance liquid chromatography (HPLC) and microbiological analysis. A simple and stability-indicating HPLC method was developed and validated for specificity, linearity, limits of detection and quantification, precision, accuracy and robustness. The liquid formulations were placed in amber PET and glass bottles, which were stored under three different conditions: at room temperature, under refrigeration and at 40 ºC. The liquid formulations were analyzed and demonstrated chemical stability for 56 days, allowing their use for long periods. However, the determination of microbiological stability showed that these formulations are prone to microbial contamination, which has dramatically reduced its stability to 7 days, in both bottles and at all evaluated temperatures.